Tourism and resilience individual, organisational and destination perspectives - Hall, Colin Michael 1961-; Prayag, Girish; Amore, Alberto (Tourism Essentials, 2017)
This book is the first authored overview of resilience in tourism and its relationship to the broader resilience literature. The volume takes a multi-scaled approach to examine resilience at the individual, organisation and destination levels, and with respect to the wider tourism system. It covers the different approaches to understanding resilience (the ecological and engineering approaches) and identifies issues with their understanding and application. The book connects issues of resilience to related key concepts such as vulnerability, adaptation, networks, systems, change and social capital. It is designed to be an upper level undergraduate and postgraduate primer on resilience in a tourism context and will be of interest to tourism researchers in planning, development, geography, impacts, sustainability, disaster management and environmental studies